2001
DOI: 10.1002/app.1853
|View full text |Cite
|
Sign up to set email alerts
|

Ethoxylated nonyl phenols and ethoxylated fatty alcohols–ceric ion redox systems for aqueous polymerization of vinyl monomers

Abstract: Ethoxylated nonyl phenols, ethoxylated fatty alcohols, and ceric ammonium nitrate redox systems were used for the polymerization of vinyl and acrylic monomers such as acrylonitrile, styrene, and acrylic acid. The initiating radical was formed on reducing organic compound which in turn initiated polymerization to give polymers containing chain ends of ethoxylated nonyl phenols and ethoxylated fatty alcohols that showed much higher water absorption. The effects of the concentration of Ce ϩ4 salt, ethoxylated non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Moreover, a larger amount of ENP in the redox reaction gave a copolymer with a higher yield and lower conductivity if the initial Ce ϩ4 concentrations were high. In our previous studies, the effect of the concentration of Ce ϩ4 and the reducing compounds have been investigated (Öz and Akar, 2001). Besides, increasing Ce ϩ4 concentrations is known to cause a significant increase in the rate of oxidative termination or primary radicals compared with the rate of initiation (Öz and Akar, 2000).…”
Section: Pigment and Resin Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a larger amount of ENP in the redox reaction gave a copolymer with a higher yield and lower conductivity if the initial Ce ϩ4 concentrations were high. In our previous studies, the effect of the concentration of Ce ϩ4 and the reducing compounds have been investigated (Öz and Akar, 2001). Besides, increasing Ce ϩ4 concentrations is known to cause a significant increase in the rate of oxidative termination or primary radicals compared with the rate of initiation (Öz and Akar, 2000).…”
Section: Pigment and Resin Technologymentioning
confidence: 99%
“…Polystyrene, polyacrylonitrile and polyacrylic acid containing chain ends of ethoxylated nonylphenol (ENP) were prepared using ceric-ENP redox initiator system (Öz and Akar, 2001). Compared with the other methods of polymerisation, aqueous redox polymerisation possesses a number of technical advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Aqueous vinyl polymerizations initiated by ceric salts alone or ceric salt‐reducing agent systems have been extensively studied 1–11. The end group profiles of the polymers that have been prepared using these systems indicated that the mechanisms of initiation and termination were largely dependent on the experimental conditions.…”
Section: Introductionmentioning
confidence: 99%